Language Accommodations in Workers' Compensation: Comparing Ontario and Quebec. (February 2022) - Premji, Stephanie; Begum, Momtaz; Medley, Alex
Workers who experience language barriers are more likely to get injured or sick because of their work and have poorer claim and return-to-work outcomes compared to other workers. To better understand the systemic factors that shape access to compensation in contexts of language barriers, we compared language accommodation policies and practices in the Quebec and Ontario workers' compensation systems. We uncovered gaps limiting access to professional interpreters in both provinces, although gaps were more pronounced in Quebec where workers were responsible for the cost of interpreters. We argue that simply improving the linguistic competence of workers' compensation systems is not sufficient to tackle access barriers and must be accompanied by efforts to address the root causes of social and economic inequities for workers who experience language barriers.